Kontynuacja czy przełom? Obraz PRL i geneza transformacji systemowej w prasie białostockiej lat 1989–1991 - Małyszko, Piotr (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2011)
The political transformation that commenced in 1989 resulted in changes in the political and economic systems of Poland. The Polish People’s Republic (PRL) ceased to exist and the Third Republic was born. While this is quite obvious from the perspective of year 2011, the content of the articles published in Bia³ystok dailies from 1989 through 1991 shows that it was not so apparent then that the year 1989 was a breakthrough. The assessment of the PRL was crucial for the process of attitude changes both in society and journalists. In 1989, Bia³ystok dailies presented a positive account of this period, while in 1991 their assessment was more complex. No one would defend the communist system as a whole any more; some painted it in dark colors, while others counterpointed its merits and weaknesses in an attempt at a balanced assessment. The main bone of contention was the political system of the PRL, the most important events of the 1980s, the great national movement that developed as ‘Solidarity’, martial law and the economic crisis. The author is interested in the Bia³ystok dailies’ attitude to these issues.